The Determinant Factors of Foreign Tourists’ Visit to Tourism Destination in North Sumatra - BATE’E, Maria Magdalena; MENDROFA, Syah Abadi; ZEGA, Yamolala; HULU, Syukur Kasieli; LELYSO, LELYSO; ZEBUA, Emmanuel (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.v10.1(33).26, 2019)
This research aims to investigate the factors influencing the rate of foreign tourists’ visit to tourism destination in North Sumatra, Indonesia. The data were collected using observation, interview, documentation study and questionnaires. The data were analysed using multiple linear regression analysis. The findings of the study indicated that the ancillary facilities are the dominant factor influencing tourists’ visit to tourism destination in North Sumatera. The factors of service quality and facilities and infrastructures provide negative influence on tourists’ visit to tourism destination.